X-linked dominant chondrodysplasia punctata (Conradi-Hünermann-Happle syndrome). - AlSoufi, L.; Fawal, H.; Al-Shehabi, Z. (European Journal of Pediatric Dermatology, 2024)
X-linked dominant chondrodysplasia punctata or Conradi-Hünermann-Happle syndrome is a rare genetic disorder characterized by skeletal dysplasia, punctate epiphyses, cataracts, and transient ichthyosis. A full-term newborn baby arrived in our department with scaly patches covering almost the entire body, prevailing on the right side of the body, with hemangioma on the right arm, dysmetria of the lower limbs, craniofacial defects including a protruding forehead, absent eyebrows and low-set ears. B-scan ocular ultrasound revealed cataract-microcornea with retinal detachment. In our case the diagnosis was made on the basis of clinical, radiological and histopathological characteristics.